Neuromuscular Complications of Targeted Anticancer Agents: Can Tyrosine Kinase Inhibitors Induce Myasthenia Gravis? Getting Answers From a Case Report up to a Systematic Review - Ziogas, Dimitrios C.; Mandellos, Dimitrios; Theocharopoulos, Charalampos; Lialios, Panagiotis-Petros; Bouros, Spyros; Ascierto, Paolo A.; Gogas, Helen (Frontiers in Oncology, 2021)
More than 40 tyrosine kinase inhibitors (TKIs) have received hematological or oncological indications over the past 20 years, following the approval of imatinib and many others are currently being tested in clinical and preclinical level. Beyond their common toxicities, no certain agent from this large class of molecularly targeted therapies was strongly associated with “off-target” impairment of neuromuscular transmission, and although myasthenia gravis (MG) is a well-characterized autoimmune disorder, only few sporadic events proven by serologically-detected causative autoantibodies and/or by positive electrophysiological tests are reported in the literature. Herein, we present the first case of anti-MUSK (+) MG in a woman with metastatic BRAF-mutant melanoma after long-term treatment with dabrafenib (BRAF inhibitor) and trametinib (MEK inhibitor). Triggered by this report, a systematic literature review was conducted, summarizing all other cancer cases that developed MG, after exposure to any type of targeted agent and regardless of the underlying malignancy. All available data on the clinical diagnosis, the potential of administered TKIs to induce a seropositive myasthenic syndrome, the immune and non-immune-mediated pathogenesis of post-synaptic damage, as well as the challenging management of this neuromuscular toxicity were collected and discussed. In the presented case, MG was confirmed by both autoantibodies and nerve-conduction tests, while its reactivation after TKIs-rechallenge supports a more than coincidental association. The following review identified 12 cancer cases with TKI-related MG in 6 case-reports and one case-series. In most of them, the myasthenia diagnosis was challenging, since the clinical symptomatology of fatigable weakness was not corroborating with consistent laboratory and electrophysiological findings. In fact, anti-AchR titers were positive in 5 and anti-MuSK only in the abovementioned individual. The symptomatology was corresponded to TKI discontinuation and standard treatment with pyridostigmine and prednisolone; intravenous immunoglobulin was added only in 3 and 2 required mechanical ventilation. In an era where TKIs will be prescribed more frequently for various malignancies, even in combinations with immune-checkpoint inhibitors, this report synthesizes their risk for neuromuscular complications and increases the clinicians’ awareness in order to extend the on-treatment and overall survival of ΤΚΙ-treated cancer patients.